Analisis Pengendalian Manajemen Kelas oleh Kepala Sekolah Terhadap Kompetensi Paedagogik Guru SD Negeri No 060874 Medan - Lubis, Parlaungan; Sinaga , Osberth; Lubis, Wildansyah (Paedagogi: Jurnal Kajian Ilmu Pendidikan (e-journal), 2025)
Classroom management control is one of the principal’s key functions in ensuring that the teaching and learning process runs effectively and meets educational standards. In practice, however, supervision is often carried out in an unsystematic manner, which affects the optimal development of teachers’ pedagogical competence. This study aims to analyze the forms of classroom management control implemented by the school principal and its impact on teachers’ pedagogical competence at SD Negeri 060874 Medan. A qualitative research approach with a case study design was employed. Data were collected through classroom observations, in-depth interviews with the principal and teachers, and document analysis of supervision records. The findings reveal that the principal’s classroom management control includes lesson observations, inspection of teaching documents, and provision of feedback. Nevertheless, such control tends to be administrative in nature and lacks strong instructional guidance, which limits its effectiveness in enhancing teachers’ ability to design learning activities, implement active strategies, and conduct authentic assessments. The study concludes that the effectiveness of classroom management control depends heavily on the consistency of supervision, the quality of feedback, and the follow-up of professional development activities. The implications highlight the need for principals to strengthen instructional supervision through coaching and reflective practices to foster the optimal growth of teachers’ pedagogical competence.